Enhancement of electrical conductivity, director relaxation frequency and slope of electro-optical characteristics in the composites of single-walled carbon nanotubes and a strongly polar nematic liquid crystal. Issue 3 (19th February 2017) - Verma, Rohit; Mishra, Mukesh; Dhar, R.; Dabrowski, R.
ABSTRACT: In the present work, single-walled carbon nanotubes (SWCNTs) were dispersed in a room temperature nematic liquid crystal 4-pentyl-4′-cyanobiphenyl at the concentration of 0.02 and 0.05 wt%. Differential scanning calorimetry and temperature-dependent dielectric studies suggest decrease in clearing temperature of the composite materials as compared to the pure material. Ionic conductivity increases by two orders of magnitude due to the dispersion of such a low concentration (0.05 wt%) of SWCNTs. Dielectric studies also show that the presence of the SWCNTs decreases the effective longitudinal as well as transverse components of the dielectric permittivity. For homeotropic aligned samples, a relaxation mechanism has been detected in the lower MHz region both for the pure as well as dispersed samples. Presence of SWCNTs increases the relaxation frequency corresponding to flip-flop motion of molecules around their short axes. From frequency-dependent dielectric studies, important dielectric parameters such as relaxation frequency, dielectric strength and distribution parameters have been determined. Electro-optical experiments show that the threshold voltage decreases and the steepness of the transmission voltage curve improves due to the dispersion of SWCNTs. GRAPHICAL ABSTRACT: